Analysis Of The Implementation Of Health Center Independence (Case Study On Health Center Bangkonol Koroncong District Pandeglang Regency) - Hermawan, Yudi; Agus Lukman Hakim (Sean Institute, 2024)
The existence of the BLUD policy has brought major changes to all UPT Health Center in the Pandeglang Regency area, including UPT BLUD Health Center Bangkonol. However, in its implementation, the Bangkonol Community Health Center, after being declared a BLUD, experienced difficulties in implementing the BLUD policy, including experiencing difficulties in the independence of the Community Health Center, especially in financial management. The BLUD at the Bangkonol Community Health Center can be said to be not optimal, there are many obstacles experienced, including human resources which are still lacking in quality and quantity. Departing from this, the researcher studied using descriptive qualitative research methods with case studies. The results of this research are discussed using the theory from Mahmudi and Masnah that to find out the implementation of the independence of BLUD Community Health Centers can be done through financial independence patterns including instructive patterns, consultative patterns, participatory patterns and delegative patterns, Community Health Center Services and Human Resource Performance. The research results show that from several indicators it was found that the UPT BLUD of the Bangkonol Community Health Center could not be said to have complete independence, seen from the first indicator that the Bangkonol Community Health Center was independent in managing its finances but was found not to be confident in managing and making e-BLUD-based financial reporting. So it was found that there was still interference from the government in financial reporting using the eBLUD application. Furthermore, in the service indicators there are several patient complaints that the service is less than optimal and slow. The next indicator regarding human resources is that there are many weaknesses in the quality and quantity of human resources which cause the implementation of the independence of the Bangkonol Health Center after becoming a BLUD to be not optimal.